1996
DOI: 10.1046/j.1526-4610.1996.3606389.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of High Sumatriptan Dosages During Episodic Cluster Headache: Three Clinical Cases

Abstract: The authors describe three patients with episodic cluster headache whose attacks were all treated with subcutaneous sumatriptan.The patients described had a high frequency of attacks (more than two per day); therefore, far higher dosage of the drug was taken than commonly used in cluster headache. The patients did not experience any particular side effects, neither during the treatment period nor on abrupt withdrawal of the drug. Moreover, neither tachyphylaxis nor addiction were observed.The authors point out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…9 Similar results were seen in 138 patients participating in the Cluster Headache Long-Term Study Group, which treated a total of 6353 attacks over 3 months. 10 No side effects were found in Centonze's three patients who were treated for at least three attacks a day for up to 4 months with sumatriptan, 6 mg, for each attack, 11 while Gobel et al, 12 in a 1-year long-term study of 52 patients, reported sumatriptan side effects but no alteration in the nature of the CH of the type found in our series.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…9 Similar results were seen in 138 patients participating in the Cluster Headache Long-Term Study Group, which treated a total of 6353 attacks over 3 months. 10 No side effects were found in Centonze's three patients who were treated for at least three attacks a day for up to 4 months with sumatriptan, 6 mg, for each attack, 11 while Gobel et al, 12 in a 1-year long-term study of 52 patients, reported sumatriptan side effects but no alteration in the nature of the CH of the type found in our series.…”
Section: Discussioncontrasting
confidence: 41%
“… 7 Studies of the efficacy and adverse effects of long‐term treatment with sumatriptan in CH are limited and report conflicting findings. 8–12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another case report observed 3 individuals with CH over 1 year, all of whom experienced 3 to 4 attacks daily and administered SC SM 6 mg for each attack. 35 Per the authors, “none of the patients showed any side effect, not even of a minor nature.” No electrocardiograph or blood pressure value alterations were detected. Regarding efficacy, the authors stated, “the efficacy of the final dose of sumatriptan for each of the 3 patients was equivalent to that observed at the beginning of the cluster.” An open, prospective study examined 52 patients with CH and cumulatively treated 2,031 attacks over the 1-year study period.…”
Section: Sumatriptanmentioning
confidence: 99%
“…Sumatriptan, 6 mg subcutaneously, was effective in 88% of the attacks, with 57% of patients becoming pain free within 15 minutes [12•, Class III]. Centonze et al [21] describe three patients who treated three or more attacks per day during bouts lasting 2 to 4 months, for a total of 166 to 278 attacks. The drug was well tolerated in these high doses.…”
Section: Diet and Lifestylementioning
confidence: 99%